The implementation of a zero-suicide framework in a child and youth mental health service in Australia: processes and learnings - Branjerdporn, Grace; McCosker, Laura K.; Jackson, Derek; McDowell, Sarah; Williams, Philip; Chand, Sandeep; Joshi, Hitesh; Pisani, Anthony R.; Stapelberg, Chris; Welch, Matthew; Turner, Kathryn; Woerwag-Mehta, Sabine (Frontiers in Psychiatry, 2024)
Suicide in children is a significant and growing problem. The "zero suicide" framework (ZSF) is one approach to suicide prevention used in health services for adults and children. This paper reports on the introduction of the first suicide prevention pathway (SPP) based on ZSF at a Child and Youth Mental Health Service (CYMHS) in Australia. It begins by describing the adaptations made to elements of the SPP originally designed for adults to meet the needs of children. Lessons learned in applying the SPP in the service are then discussed. The aim is to inform and improve practice in the use of zero suicide approaches in child and youth mental health settings in Australia and worldwide.